2015
DOI: 10.1073/pnas.1503058112
|View full text |Cite
|
Sign up to set email alerts
|

Pel is a cationic exopolysaccharide that cross-links extracellular DNA in the Pseudomonas aeruginosa biofilm matrix

Abstract: Biofilm formation is a complex, ordered process. In the opportunistic pathogen Pseudomonas aeruginosa, Psl and Pel exopolysaccharides and extracellular DNA (eDNA) serve as structural components of the biofilm matrix. Despite intensive study, Pel's chemical structure and spatial localization within mature biofilms remain unknown. Using specialized carbohydrate chemical analyses, we unexpectedly found that Pel is a positively charged exopolysaccharide composed of partially acetylated 1→4 glycosidic linkages of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
557
3
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 520 publications
(605 citation statements)
references
References 43 publications
20
557
3
6
Order By: Relevance
“…Psl and Pel are often associated with nonmucoid strains and are necessary for biofilm formation (34). The anionic alginate could interact electrostatically with Bac7(1-35) enhancing the binding of the peptide, while the cationic Pel could repulse it (35). In this respect, it has been shown that alginate in solution inhibits the antimicrobial activity of structurally different peptides, including Bac7(1-35) (36).…”
Section: Mode Of Action Of Bac7(1-35) Against P Aeruginosamentioning
confidence: 99%
“…Psl and Pel are often associated with nonmucoid strains and are necessary for biofilm formation (34). The anionic alginate could interact electrostatically with Bac7(1-35) enhancing the binding of the peptide, while the cationic Pel could repulse it (35). In this respect, it has been shown that alginate in solution inhibits the antimicrobial activity of structurally different peptides, including Bac7(1-35) (36).…”
Section: Mode Of Action Of Bac7(1-35) Against P Aeruginosamentioning
confidence: 99%
“…In comparison, P. aeruginosa has the genetic capacity to produce three biofilm exopolysaccharides: alginate, Psl and Pel (16). GAG shares several similarities with Pel, which has been identified as a cationic heteroglycan composed of 1,4-linked GalNAc and N-acetyl-D-glucosamine (GlcNAc) (17). Like GAG, the cationic nature of Pel results from partial deacetylation of the polymer (17).…”
mentioning
confidence: 99%
“…GAG shares several similarities with Pel, which has been identified as a cationic heteroglycan composed of 1,4-linked GalNAc and N-acetyl-D-glucosamine (GlcNAc) (17). Like GAG, the cationic nature of Pel results from partial deacetylation of the polymer (17). Most clinical and environmental isolates of P. aeruginosa use Pel and Psl during biofilm formation (18).…”
mentioning
confidence: 99%
“…Further, it was recently shown that the presence of a filamentous bacteriophage can result in conversion of the matrix into liquid crystalline structure, which is linked to antibiotic resistance and the physical stability of the biofilm matrix (Secor et al ., 2015). As the matrix components are identified, it may be possible to develop specific visualization approaches, such as the Wisteria floribunda lectin that specifically recognizes the Pel polysaccharide (Jennings et al ., 2015), so that the localization and interactions between EPS components can be studied. This may also help explain why the biofilm is more than the sum of its individual parts.…”
mentioning
confidence: 99%